2021
DOI: 10.1002/onco.13745
|View full text |Cite
|
Sign up to set email alerts
|

Novel SLC12A2-ROS1 Fusion in Non-Small Cell Lung Cancer with a Significant Response to Crizotinib: The Importance of Choosing the Appropriate Next-Generation Sequencing Assay

Abstract: Identifying the druggable target is crucial for patients with non-squamous advanced non-small-cell lung cancer (NSCLC). This case report adds to the spectrum of ROS1 fusion cases described in NSCLC. We describe a novel SLC12A2-ROS1 rearrangement that has not been previously reported in other cancers, a fusion that has clinical and radiological sensitivity to crizotinib. We detected the SLC12A2-ROS1 fusion by FISH and it was confirmed through hybrid capture-based next-generation sequencing; however, the fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“… 3 , 5 , 8 , 16 The present case provides the second report in the literature that NSCLCs harboring SLC12A2-ROS1 fusions can respond to second-line crizotinib as well, with our patient remaining progression-free for 21 months now. 17 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 3 , 5 , 8 , 16 The present case provides the second report in the literature that NSCLCs harboring SLC12A2-ROS1 fusions can respond to second-line crizotinib as well, with our patient remaining progression-free for 21 months now. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Although it is unknown whether SLC12A2-ROS1 fusion occurs more frequently in this subgroup of patients, our report reinforces the concept that not only this fusion is oncogenic but also confers sensitivity to ROS1 TKIs, which could theoretically contribute to tailor clinical decision for individuals diagnosed with lung tumors harboring this alteration. 17 , 19 Interestingly, the case reported by Rodriguez-Antolin and colleagues displays some intriguing similarities with our case, for instance, (1) very young age of diagnosis (21 vs 26 years old, which could contribute to delay the diagnosis), (2) symptomatic and high-volume lung involvement at diagnosis of advanced disease, (3) refractoriness to frontline chemoimmunotherapy with subsequent clinical deterioration, as well as (4) fast and deep response to crizotinib. In this specific case, the ROS1 fusion breakpoint occurred in exon 36, as opposed to our case and Li et al’s 19 description (introns 35 and 34, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The (c-ros oncogene1) ROS1 rearrangements, which drive malignant transformation of NSCLC, affect approximately 0.7-1.7% NSCLC patients (91). The fusion partners include CD74, SLC34A2, FIG, TPM3, SLC12A2, CCDC6, and SDC4, while CD74-ROS1 fusion is the most prevalent phenotype in NSCLC (92,93). Gou et al demonstrated that CD74-ROS1 mutation could lead to EMT and enhance the NSCLC invasion and migration ability by upregulating Twist1 (94).…”
Section: Ros1 Rearrangementsmentioning
confidence: 99%